Correlation between Experiential Learning and Optimism among College students - Shemaili, Noora Bani (2013)
The purpose of this study is to investigate if there is a relationship between experiential learning and optimism among college students. The field of study is one of the female federal colleges in the United Arab Emirates. The sample size is 162 students which can be considered numerically meaningful for correlational study. The literature supports the study through the theories and other studies. A mixed method approach was used in this study centred on questionnaire and interviews to reach final conclusions and resulting recommendation. The mixed method approach gives a much more holistic view of the many issues directly related to the experiential learning and optimism and its impact on college students. The collected data and analysis provided by the researcher present clear evidence of the compared two principals. The findings proved that students involvement in the experiential learning process has a positive, lasting impact on student emotions particularly the level of optimism.